PELUANG BISNIS KATERING PADA WISATA RELIGI WALI 5 - Erik Bisri Alamsyah; Eny Rochmatulaili (Fakultas Ekonomi Universitas Yos Soedarso, 2019)
Â Pilgrimage Tourism is Always a Phenomenon. This Condition Continues In Ramadan. Pilgrimage of the Guardian's Tomb 5 So far Can Bring a Big Tourist, There is a Very Promising Economic Turnover in a Year. Referring to the 2014 Minister of State's Data, Walisongo's Grave Can Attract Many Tourists for Pilgrimage. Within a Year the Total Visit of Pilgrimage Archipelago Tourists Reaches 12.2 Million People, More Attractive There Are 3,000 Foreign Tourists Who Also Visit Walisongo's TombThis study uses a qualitative approach in which the writer tries to explore the depth of data obtained from interviews with Respondents so that the data obtained becomes valid for analysis. The location of this study is a place of religious tourism in Sunan Ampel Religious Tourism Park. The research data includes three data, namely primary data, secondary data, and tertiary data. After the data is obtained, then it will be analyzed by descriptive-qualitative analysis techniques.The results of the questionnaire show that most consumers feel interested in catering to handle requests from consumers. This is evidenced by the results of interpretation of the demand for catering with a score of 70%.